Degree of commitment of science books in the Hashemite Kingdom of Jordan to the basic stage in grades (4-6) of the Brunner spiral model in curriculum design in plant subjects. - Qablan, Ahmed Barham Khalaf (Journal of Educational and Psychological Sciences, 2019)
This study aimed at revealing the degree of commitment of science books in the Hashemite Kingdom of Jordan in grades (4-6) in the basic Bruner spiral model in the design of the curriculum and to recognize the repetition of scientific concepts and how to move from one row to another. The results showed a wide horizontal breadth in the level of the treatment of different fields of knowledge and concepts at a high rate of mental level and developmental stage of the students. It was graduated from easy to composite and from general to private. All science books in the classes. The concept of integration has emerged so clearly that the content and experiences have been linked with appropriate activities in terms of clarifying and deepening the concepts and in terms of suitable for the development stage of the students and a high percentage of their environment as well as their transition from the tangible (in the lower grades) to the abstract (in the upper grades). In terms of continuity and continuity, the percentage was high. In the light of the results, a number of recommendations and proposals were presented to address the deficiencies in the curricula of the sciences and the various curricula in the Kingdom of Jordan.